PELAKSANAAN PROGRAM PENGELOLAAN LINGKUNGAN HIDUP KABUPATEN INDRAGIRI HULU ( STUDI KASUS PENGKAJIAN DAMPAK LINGKUNGAN SUNGAI BATANG KUANTAN DESA PASIR KERANJI) - Prayogi, Doan; Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Environmental policy is a manifestation of sustainable management and utilization of natural resource and environment. In Batang Kuantan River Pasir Keranji Village there are many mining activities that cause river pollution. Based of research showed Environmental Impact Assessment Program by environmental Agency is not optimally yet. Based on this, researcher are interested to studying how the Implementation of Environmental Management Program of Indragiri Hulu Regency ( Case Study Environmental Impact Assessment Program Batang Kuantan River Pasir Keranji Village). Theoretical concept used is implementation in Van Meter and Van Horn (2008) who said that there was several variables that affected the performanced of the public policy implementation. This research used qualitative method by using snowball as information and the data analys thecnique by using triangulation technique. Result of the research showed that Implementation of Environmental Management Program of Indragiri Hulu Regency ( Case Study Environmental Impact Assessment Program Batang Kuantan River Pasir Keranji Village) is not optimally yet. This is caused lack of resources, infrastructure, insufficient funds. Social and economic factors of society become obstacle in Implementation of Environmental Management Program especially Environmental Impact Assessment Program in Batang Kuantan River. Keyword : Environmental Management Program, Implementation, Batang Kuantan River.